Pretend Play in an Interactional Context : Emergence and Assessment of Preschool Children’s Social Pretend Play and its Role in their Social Development - Jaggy, Ann-Kathrin (My University, 2020)
It has been stated that pretend play might be beneficial for children’s social development. However, although much research has been done on children’s pretend play, there is as yet no consensus on the role of pretend play in children’s social development. This thesis starts with an overview of research on children’s pretend play and its social developmental significance, and provides a more detailed examination of what features of pretend play exactly are thought to promote social development. Existing literature and research suggest that it is high-quality social pretend play, in particular, that is associated with children’s social development. Achieving high-quality social pretend play in children’s play might therefore be the key to unlocking the beneficial effect of pretend play for children’s positive social development. However, only little is known about the role of the social context in preschooler’s pretend play and whether promoting children’s social pretend play quality leads to positive social development. The overall aim of this thesis is to contribute to a better understanding of children’s pretend play in a social interactional context and its social developmental significance. For this purpose, three studies were conducted that consider both, individual child characteristics, and the social context. Study 1 validated and compared three recently developed assessment methods for children’s social pretend play competence: A standardised role-play test (Tools of the Play Scale), a social pretend play situation with a peer (Dyadic Pretend Play Assessment), and an educator report (Reported Pretend Play Competence). N = 64 children (Mage = 46.4 months, SD = 3.8) participated in the study, which showed that all three instruments are appropriate tools for the assessment of children’s social pretend play competence, but also that they cover different facets of social pretend play competence. An underlying second-order factor of social pretend play competence was identified. Study 2 investigated individual as well as interactional conditions for the emergence of high-quality social pretend play during dyadic peer play. N = 57 children (Mage = 46.5 months, SD = 3.8) participated in the study, which showed that children's social pretend play quality is determined to the same degree by the child and by the specific pairing of two children. Further, results showed that the quality of children's social pretend play benefited from having older and more advanced play partners. The study highlighted the importance of the dyadic constellation for the emergence of social pretend play quality during peer play. Study 3 investigated whether promoting children’s social pretend play quality during play fosters their social development. N = 211 children (Mage = 43.3 months, SD = 6.5) participated in the study, which showed that actively promoting children’s social pretend play quality through play tutoring fosters children’s social behavioural skills and their positive peer relationships. No effects were found for children’s social-cognitive and emotional skills. These findings are discussed against the backdrop of the dissertation’s overall aim. They indicate the importance of children’s peers for the emergence of social pretend play quality, and highlight the potential that promoting children’s social pretend play might provide for their social behavioural skills and peer relationships. The thesis also provides a methodologically sound foundation for further research on children’s social pretend play.
Keywords: social pretend play, social competence, emotional skills, social skills, socialcognitive skills, intervention; 150